Impact of the Covid-19 on Fast Food Business in Kathmandu - Dahal, Ananta Raj (Historical Journal, 2023)
Corona-virus is a very dangerous virus in the world. It affects the overall human activities in Nepal. This research article tries to analyze the impact of the Coronavirus on the fast food business in Kathmandu. The fast food business is very popular in Kathmandu, it provides services for different levels of people and also provides employment opportunities as well as increasing economic activities. Due to Coronavirus, these economic activities, through the primary information collected in certain sample areas for analysis, affect the economy. This study is helpful to know the current situation of the fast food business of our country and the economic impact of the coronavirus on the income of the fast food business. After analyzing the information provided by the respondent through the questionnaire survey Coronavirus reduced employment opportunities, the business of the fast food market, and the income level of the entrepreneur as well as the employee people in the sample area. It is concluded that the virus hurt the fast food business sector in Kathmandu.